A cross-sectional study of Mycoplasma genitalium infection and correlates in women undergoing population-based screening or clinic-based testing for Chlamydia infection in London. Issue 2 (6th February 2014) - Svenstrup, H F; Dave, S S; Carder, C; Grant, P; Morris-Jones, S; Kidd, M; Stephenson, J M
Abstract : Objective: To determine Mycoplasma genitalium infection and correlates among young women undergoing population-based screening or clinic-based testing for Chlamydia infection. Design: Cross-sectional study. Setting: National Chlamydia Screening Programme (NCSP) and two London sexually transmitted infection (STI) clinics. Participants: 2441 women aged 15–64 years who participated in the NCSP and 2172 women who attended two London STI clinics over a 4-month period in 2009. Outcome measures: (1) M genitalium prevalence in defined populations (%). (2) Age-adjusted ORs (aORs) for correlates of M genitalium infection. Results: The overall frequency of M genitalium and Chlamydia trachomatis was 3% and 5.4%, respectively. Co-infection was relatively uncommon (0.5% of all women); however 9% of women with C trachomatis also had M genitalium infection. M genitalium was more frequently detected in swab than urine samples (3.9 vs 1.3%, p<0.001) with a significantly higher mean bacterial load (p ≤ 0.001). Among NCSP participants, M genitalium was significantly more likely to be diagnosed in women of black/black British ethnicity (aOR 2.3, 95% CI 1.2 to 4.5, p=0.01). M genitalium and C trachomatis and were both significantly associated with multiple sexual partners in the past year (aOR 2.4, 95% CI 1.3 to 4.4, p=0.01 and aOR 2.0, 95% CI 1.4 to 2.8, p<0.01). Among STI clinic attendees, M genitalium was more common in women who were less than 25 years in age. Conclusions: M genitalium is a relatively common infection among young women in London. It is significantly more likely to be detected in vulvovaginal swabs than in urine samples. Co-infection with Chlamydia is uncommon. The clinical effectiveness of testing and treatment strategies for M genitalium needs further investigation.